Development of Animation Learning Videos Based on Ethnomathematics Using Plotagon on Spldv Material - Raden Roro Shinta Luthfiana Yasri; Endah Wulantina (Journal of Medives: Journal of Mathematics Education IKIP Veteran Semarang)
The learning media used at SMP Negeri 6 Metro are textbooks the school provides. So, students are less interested in mathematics lessons. The results of previous research show that students need attractive media presentations that contain images, can be accessed via the Internet, and are based on Lampung culture. This research aims to develop an ethnomathematics-based animated video using plotagons on SPLDV material based on its feasibility and attractiveness as a learning medium. The method used in this research is Research and Development (R&D) with a 4D development model. Data were collected through interviews, observation, and distribution questionnaires. This research data comes from two material experts, two media experts, and two cultural experts. The subjects in this research were 25 students in class VIII of SMP Negeri 6 Metro. The research results show that animated videos are suitable for use as learning media with material expert validation of 92.71%, media 84.62%, and culture 90.63% with “very worthy” criteria, and student responses received a percentage of 91.32% with “very interesting” criteria. Based on the research results, animated videos can help with mathematics learning at school.